Tinjauan Kelengkapan Pengisian Sertifikat Penyebab Kematian di Rumah Sakit Umum H. Adam Malik Medan Tahun 2019 - Esraida Simanjuntak; Anggraeini Ginting (Jurnal Rekam Medis dan Informasi Kesehatan, 2019)
The cause of death is all diseases, conditions of illness, or injuries that cause or facilitate death, and accidents or violence that cause such injuries. The cause of death data in the cause of death certificate is used as the main source of hospital mortality data. Quantitative analysis is a review or review of certain parts of the contents of the medical record with the intention of finding specific deficiencies related to recording medical records. Quantitative analysis consists of four components, namely the identification review, important report review, authentication review and record review. The purpose of this research was to determine the percentage of completeness in completing certificates of cause of death. This type of research is a description of the check-list sheet method and observation. The research site was conducted at H. Adam Malik General Hospital in Medan. When the research was conducted in April-May 2019. The population and sample used were data on patient deaths and certificates of cause of death in March. Based on the results of the research, obtained the calculation of the percentage of completeness of the certificate of the cause of death based on an identification review of 40.5%, the completeness based on the important report review of 28.9%, the completeness based on the 98.5% authentication review and the review recording can be read and clear at 85, 5%. The conclusion of this research is that a low percentage of completeness in the identification review and review of the report is important because of the large number of components that must be filled so that it requires more time. The suggestion from this research is that officers should be able to complete the certificate of causes of death completely and clearly.